Dante and the Dynamics of Textual Exchange : Authorship, Manuscript Culture, and the Making of the 'Vita Nova' - Todorović, Jelena (Professor of Italian literature) (Book collections on Project MUSE., 2016)
"Dante and the Dynamics of Textual Exchange is the first book-length study to explore the question of poetry and genre in Dante's Vita Nova (ca. 1292-1294). In paying particular attention to complex and multifaceted interactions between different cultures in Italy in the thirteenth century, this study illuminates the multicultural and plurilinguistic society transitioning from the feudal court to the modern city-state, advanced by the rising mercantile class. Working at the intersection of textual, material, and cultural elements, this study complements the current state of scholarship by providing information and answers informed by an in-depth analysis of the manuscript culture and its role in the birth and development of European vernacular traditions. Furthermore, Dante and the Dynamics of Textual Exchange expands the literature's understanding of the dynamics between a text and its material support by looking at this relationship within a broader framework of intercultural exchange, which suggests an increased dynamics and fluidity between cultures"--